Hyperthermia and fatigue - Nybo, L. (Journal of Applied Physiology, 2008)
The present review addresses mechanisms of importance for hyperthermia-induced fatigue during short intense activities and prolonged exercise in the heat. Inferior performance during physical activities with intensities that elicit maximal oxygen uptake is to a large extent related to perturbation of the cardiovascular function, which eventually reduces arterial oxygen delivery to the exercising muscles. Accordingly, aerobic energy turnover is impaired and anaerobic metabolism provokes peripheral fatigue. In contrast, metabolic disturbances of muscle homeostasis are less important during prolonged exercise in the heat, because increased oxygen extraction compensates for the reduction in systemic blood flow. The decrease in endurance seems to involve changes in the function of the central nervous system (CNS) that lead to fatigue. The CNS fatigue appears to be influenced by neurotransmitter activity of the dopaminergic system, but may primarily relate to inhibitory signals from the hypothalamus arising secondary to an increase in brain temperature. Fatigue is an integrated phenomenon, and psychological factors, including the anticipation of fatigue, should not be neglected and the interaction between central and peripheral physiological factors also needs to be considered.